A pseudo-capacitive chalcogenide-based electrode with dense 1-dimensional nanoarrays for enhanced energy density in asymmetric supercapacitors. Issue 26 (25th May 2016) - Lee, Young-Woo; Kim, Byung-Sung; Hong, John; Lee, Juwon; Pak, Sangyeon; Jang, Hyun-Sik; Whang, Dongmok; Cha, SeungNam; Sohn, Jung Inn; Kim, Jong Min
Abstract : Well-arrayed 1-D CuS structures with nanosized grains and high grain boundaries exhibit superior pseudo-capacitive properties. Abstract : To achieve the further development of supercapacitors (SCs), which have intensively received attention as a next-generation energy storage system, the rational design of active electrode materials with an electrochemically more favorable structure is one of the most important factors to improve the SC performance with high specific energy and power density. We propose and successfully grow copper sulfide (CuS) nanowires (NWs) as a chalcogenide-based electrode material directly on a Cu mesh current collector using the combination of a facile liquid–solid chemical oxidation process and an anion exchange reaction. We found that the as-prepared CuS NWs have well-arrayed structures with nanosized crystal grains, a high aspect ratio and density, as well as a good mechanical and electrical contact to the Cu mesh. The obtained CuS NW-based electrodes, which were binder- and conductive material-free, exhibit a much higher areal capacitance of 378.0 mF cm −2 and excellent cyclability of approximately 90.2% retention during 2000 charge/discharge cycles due to their unique structural, electrical, and electrochemical properties. Furthermore, for practical SC applications, an asymmetric supercapacitor is fabricated using active carbon as an anode and CuS NWs as a cathode, and exhibits the good capacitance retention of 91% during 2000 charge/discharge processes and the excellent volumetric energy density of 1.11 mW h cm −3 compared to other reported pseudo-capacitive SCs.